Effect of Terminalia Arjuna (Arjun) Bark on Serum Aspartate Aminotransferase and Alanine Aminotransferase in Isoniazid Induced Hepatotoxicity in Wistar Albino Male Rats - Iqram, Towhidul; Begum, Dilruba; Hossain, Farzana; Fatema, Kaniz; Halder, Shweta; Akter, Khalada; Siddique, Md Asraful Alam (Eastern Medical College Journal, 2025)
Background: Liver diseases have become a major problem worldwide and are associated with significant morbidity and mortality. Many of the new drugs used for the treatment for liver diseases. They are costly and have limited efficacy. Therefore, plant derived compounds which are accessible and do not require laborious pharmaceutical synthesis seem to be helpful for treating liver diseases. The Objective of the study is to observe the hepatoprotective effect of Terminalia arjuna on serum aspartate aminotransferase and serum alanine aminotransferase in isoniazid induced hepatotoxicity in Wistar albino male rats. Materials & Methods: This experimental study was carried out in the department of physiology, Dhaka Medical College, Dhaka from July 2021 to June 2022. A total number of twenty-four (24) apparently healthy Wistar albino male rats (age 90-120 days) weighing between 150-200 gm were selected for the study. After acclimatization for 7 days, they were divided into control groups and experimental groups. Control group was subdivided into group A (baseline control group) and group B (isoniazid only treated group). The experimental group was subdivided into group C (Isoniazid pretreated and Terminalia arjuna treated group) and group D (Isoniazid pretreated and Terminalia arjuna treated group). On day 22, all the animals were sacrificed, and blood samples were collected from the heart. The liver samples were excised preserved in 10% formalin for histology. Serum AST and ALT were estimated. Data were presented as mean ±SD. One way ANOVA or Kruskal Walli’s test followed by Bonferroni test was done. Results: The serum ALT and AST level were significantly increased in group B (135.3±8.1, 119.5±8.5) in comparison with that of group A (42.8±5.8, 40.5±9.4); group C (58.1±19.9, 54.1±13.9) and group D (55.5±14.1, 46.1±12.7). No significant difference was found in serum ALT and AST levels between group A and group C; group A and group D and between group C and group D. Conclusion: The results of this study may be suggested that Terminalia arjuna has hepatoprotective effect on Isoniazid induced liver damage in Wistar albino male rats. Eastern Med Coll J. July 2025; 10 (1): 18-22